Role of Oxytocin and Cortisol Simultaneous with the Cellular Oxidative Stress in Preventing Pregnancy in Females with Un Known Infertile Cause Who Undergone to Artificial Fertilization - Rasha Hasan Jasim (Journal of Global Pharma Technology, 2018)
Eighty two women were enrolled in the present study, they are classified into two groups, and the first included 42 females aged 23 – 42 years who had never a normal pregnancy. They had to undergo IVF with a regular 6 month menstrual cycle before applying for an IVF at the Infertility Treatment Center in Sadder City Medical in Najaf, Iraq. The second group included 40 females with age rang 22 – 40, were selected as control, results of the present work were summarized in the below table. Oxytocin and cortisol levels were evaluated in the present work in addition to several oxidants and antioxidant parameters. Results of the study showed significant elevation in the BMI (Mean ± S.D.) at females suffered unknown infertile cause comparison to healthy females and this elevation was directly correlated to pregnancy prevention. Outcomes recorded statistically significant decrease in the oxytocin and SOD Activity (U/dl) in the sera of females who submitted for artificial insemination, while all of cortisol, MDA, NO, and Cp concentration seemed to be higher in the sera of patient’s women than their corresponding in the control group. Results of the study illustrated highly significant correlation between oxytocin and cortisol (r = - 0.735 at p = 0.001), as well as oxytocin and NO (r = - 0.779 at p = 0.001, and between MDA and NO (r = 0.882 at p = 0.001). More than; the study showed there are significant correlation (r = 0.832) between Cortisol with NO, and MDA with SOD Activity (r = -859) at p = 0.005. The study concludes that oxytocin could directly affect in the preventing of normal pregnancy moreover in decrease of the success of the artificial insemination process.    Key words: Oxytocin, Cortisol, Artificial Insemination, Female Infertility, Oxidative Stress, SOD activity, NO, MDA.